Developing an Evaluation Model for Junior Planner Training to Enhance Planner Competency - Ivan Budi Susetyo; V. Rudy Handoko; Joko Widodo (East Asian Journal of Multidisciplinary Research, 2023)
Human resource planners must be managed effectively by providing knowledge, skills, and expertise that are more in line with their needs, one of which is through functional training for first-level planning experts. To determine the results, impacts, and benefits obtained from the training provided, evaluation is necessary. The aim of this research is to analyze the effectiveness of functional training for first-level planning experts, determine the extent of the influence of functional training for first-level planning experts on competence, and describe the development of an evaluation model. This research is a mixed methods study with a sequential explanatory model. The sampling technique used purposive sampling with a sample size of 23 people. The results show that functional training for first-level planning experts can effectively improve knowledge, skills, and work attitudes through the learning process and provide benefits for both personal and career development. The influence of training on competence is 78.7%, with the development model of the four levels of training evaluation and perceived training benefit as the evaluation method forming an integrative evaluation model consisting of 5 levels of evaluation as a novelty product about training evaluation, including reactions, learning, behavior, results, and benefits.